Alun-Alun Lama dan Wilhelmina Plein Ruang Terbuka kota di Pusat Pemerintahan Lokal dan Kolonial di Semarang - R Siti Rukayah; Septana Bagus Pribadi; Annica Etenia (Department of History, Faculty of Humanities, Diponegoro University, 2021)
Design of the government city center in the traditional period has proven to reveal the richness of Indonesian culture. One of them is evidenced by the values of local wisdom that still maintained from generations even though various challenges have been faced, including the penetration of foreign influences. The traditional center of government is reflected in Semarang's Old City Square [Alun-Alun Semarang]. Its existence coincided with the center of colonial administration (Kantor Gouverneur van Java's Noord-Oostkust, 1754–1761) on Jalan Bojong (now Jalan Pemuda Semarang) which lasted until the 1970s. Unfortunately, after the 1970s, the alun-alun and the traditional government center (Kanjengan) disappeared and only left a cultural heritage in the form of mosque buildings and the dhugderan tradition mostly became an icon of the identity of traditional cities in Java. By using the historical method in relation to the use of contemporary sources, this study reveals the existence of the alun-alun as an open space for the traditional rulers and Taman Wilhelmina Plein as an open space for the colonial government, both of them were located in the same city corridor. The Jalan Bojong Corridor is part of de Groote Postweg, Jalan Raya Pos stretched from Anyer to Panarukan. In Semarang, this road connects the fort area which is now the Old City and Alun-Alun Semarang. The interesting issue is the dualism of road section in colonial government is reflected and it is side by side with the traditional center of government.